Determinacion de la incidencia de afidos en zonas utilizadas para la produccion de semilla de papa - Perez, K.=700 1 Garcia, D.
(En, Es)
Ilus., 10 ref
Keywords: POBLACION ANIMAL; AFHIDOIDEA; PRODUCCION DE SEMILLAS; PAPA; DINAMICA DE LA POBLACION; CUBA; AFIDOS